Maternal and perinatal outcome in eclampsia at a tertiary care center - Dalal, Monika; Singh, Sandhya; Chauhan, Meenakshi; Nanda, Smiti; Dalal, Jagjit; Madan, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is the occurrence of hypertension in combination with proteinuria, developing after 20 weeks gestation in a previously normotensive non-proteinuric patient. The objective of this study was to study the prevalance of eclampsia at PGIMS, Rohtak. To study the clinical profile, maternal and perinatal outcome in eclamptic patients. Methods: This is a retrospective study and case records of all eclampsia cases were analysed from the study period of January 2018 to December 2018. Results: There were 113 cases of eclampsia out of 11,661 deliveries and prevalence of eclampsia was calculated to be 0.96%. Majority of the patients were not registered 95.57%. 58% of patients were Primigravidas. 56% of the patient in the age group of 21-25 years. Antepartum, intrapartum and postpartum eclampsia were 71%, 1.7% and 27% respectively. Caesarean section was the preferred mode of delivery and was performed in 57% cases. ICU admission was required in 25% and remaining cases were managed in general/eclampsia ward. All patients received MgSO4 by Zuspan regimen. 12% patient developed HELLP syndrome and pulmonary oedema developed in 6% patient. There were a total of 3.5% maternal deaths during the study period. Total percentage of perinatal deaths due to eclampsia was 23%. Conclusions: Eclampsia continues to be one of the prime etiological factors for maternal and perinatal morbidity and mortality. This is due to lack of proper antenatal care, low socioeconomic condition and lack of education. Regular antenatal checkup, early recognition and proper management are vital to tackle this challenge. MgSo4 is the anticonvulsant of choice and Zuspan regimen of MgSO4 is effective in the management of eclampsia.